The Role of Satisfaction Intervening of Halal Label on Purchasing Decision: Case Kapal Api Coffee - Lestari, Putri; Budiman, Andika Nuraga (SAN Scientific, 2024)
This research was conducted with the aim of examining the effect of the halal label on customer loyalty through purchasing decisions and customer satisfaction as a mediating factor. This research was designed as explanatory research. The population in this study was Kapal Api coffee customers in Kelapa Gading, with a total sample size of 120 respondents. The sampling technique used is non-probability sampling. Data collection was carried out using the survey instrument questionnaire method through the Google Form page. The data analysis method uses Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4 software. The results show that the halal label has a positive and significant effect on customer loyalty; customer satisfaction does not affect customer loyalty; the effect of the halal label on customer loyalty is not mediated through customer satisfaction as a mediating factor; and purchasing decisions cannot partially mediate the relationship between halal labels and customer loyalty. The managerial implication of the research is the importance of strengthening marketing strategies that prioritize halal labels to increase customer loyalty. Management needs to ensure that all their products have clear and reliable halal certification while focusing on increasing customer satisfaction through product innovation and adequate service.